Courses

# RD Sharma Solutions for Class 8 Math Chapter 6 - Algebraic Expressions and Identities (Part-2) Class 8 Notes | EduRev

## RD Sharma Solutions for Class 8 Mathematics

Created by: Abhishek Kapoor

## Class 8 : RD Sharma Solutions for Class 8 Math Chapter 6 - Algebraic Expressions and Identities (Part-2) Class 8 Notes | EduRev

The document RD Sharma Solutions for Class 8 Math Chapter 6 - Algebraic Expressions and Identities (Part-2) Class 8 Notes | EduRev is a part of the Class 8 Course RD Sharma Solutions for Class 8 Mathematics.
All you need of Class 8 at this link: Class 8

#### Question 4: Find each of the following product: #### Answer 4: To multiply algebraic expressions, we use commutative and associative laws along with the the law of indices, that is, am×an=am+nam×an=am+n.

We have:    Thus, the answer is 1/6 x3y2z216x3y2z2.

#### Question 5: Find each of the following product: #### Answer 5: To multiply algebraic expressions, we use commutative and associative laws along with the law of indices, i.e., am×an=am+nam×an=am+n.

We have:  (x×x2)×(y2×y)×(z×z2) ×(x1+2)×(y2+1)×(z1+2)

= - 91/15 x3y3x3

Thus, the answer is = - 91/15 x3y3x3

#### Question 6: Find each of the following product: #### Answer 6: To multiply algebraic expressions, we use commutative and associative laws along with the law of indices, i.e., am×an=am+nam×an=am+n.

We have:  ×(x3×x)×(z×z2)×y ×(x3+1)×(z1+2)×y

9/10 x4yz3=910x4yz3

Thus, the answer is  9/10 x4yz3=910x4yz3

#### Question 7: Find each of the following product: ####  (a2×a3)×(b2×b2)×c2 (a2+3)×(b2+2)×c2

= - 1/6 a5b4c2

Thus, the answer is = - 1/6 a5b4c2

#### Answer 8: To multiply algebraic expressions, we use commutative and associative laws along with the law of indices, i.e., am×an=am+nam×an=am+n.We have: =(7×1/4)×(x×x2)×(y×y)×z

=(7×1/4)×(x1+2)×(y1+1)×z

= 7/4 x3y2z

Thus, the answer is  7/4 x3y2z